Peripartum Cardiomyopathy Presenting as Bradycardia - Elisabeth Codsi; Carl H. Rose; Marysia S. Tweet; Sharonne N. Hayes; Patricia J. M. Best; Lori A. Blauwet (Hindawi Limited, 2017)
Peripartum cardiomyopathy (PPCM) is a disease that typically affects young otherwise healthy women. As PPCM is associated with significant mortality, timely diagnosis is necessary to ensure appropriate care. To our knowledge, this represents the first reported case of PPCM presenting as symptomatic bradycardia. We describe the patient's clinical presentation and relevant findings and review the potential etiology and ramifications of bradycardia in patients with PPCM.